2020
DOI: 10.1016/j.biocon.2020.108436
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of wild herbivore species richness and occupancy across a savannah rangeland: Implications for conservation

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 57 publications
0
36
0
Order By: Relevance
“…The ongoing human population growth in East Africa limits options to expand the extent of fully protected areas (Caro & Davenport, 2016), which urges conservationists to develop, test, and implement human–wildlife coexistence models to counteract the biodiversity crisis (Crego et al., 2020; Tyrrell, du Toit, & Macdonald, 2020; Western et al., 2020). Our case study shows that wildlife populations in a managed pastoral area remained constant over a 17‐year span.…”
Section: Resultsmentioning
confidence: 99%
“…The ongoing human population growth in East Africa limits options to expand the extent of fully protected areas (Caro & Davenport, 2016), which urges conservationists to develop, test, and implement human–wildlife coexistence models to counteract the biodiversity crisis (Crego et al., 2020; Tyrrell, du Toit, & Macdonald, 2020; Western et al., 2020). Our case study shows that wildlife populations in a managed pastoral area remained constant over a 17‐year span.…”
Section: Resultsmentioning
confidence: 99%
“…Large mammal biodiversity is being lost at an unprecedented rate across the globe, and the repercussions of these losses for ecosystem function and human well‐being have garnered increasing attention (Cardinale et al., 2012; Díaz et al., 2006; Johnson et al., 2017; Johnson & Thieltges, 2010). We investigated the effects of the loss of large herbivorous mammals on mosquito ecology and evaluated the implications for vector‐borne zoonotic disease transmission in an ecosystem where humans and wildlife coexist, but where large herbivore populations are threatened by the intensification of livestock production and other anthropogenic activities (Crego et al., 2020; Ogutu et al., 2016). We found that the exclusion of large wild mammals changed key aspects of mosquito ecology and behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the responses of eland may reflect those of species with comparable feeding strategies, such as Grant's gazelle Nanger granti and impala Aepyceros melampus (Kartzinel et al, 2019;Kartzinel and Pringle, 2020). Cattle grazing may also facilitate smaller-bodied short grass specialists, such as Thomson's gazelle Eudorcas thomsoni and warthog Phacochoerus africanus (Bhola et al, 2012;Ogutu et al, 2014;Crego et al, 2020;Wells et al, 2021a).…”
Section: Wild Mesoherbivore Habitat Use Responses To Cattle Stocking ...mentioning
confidence: 99%